Fitzcarraldo [videorecording (DVD)] - Herzog, Werner, 1942-; Kinski, Klaus; Cardinale, Claudia, 1939- (Anchor Bay Entertainment [distributor, 1999)
Story of a man obsessed with a dream to build his own personal opera house in a remote Peruvian town.